Aspek Kognitif Penyandang Disabilitas - Dwi Sari Usop; Suniati Suniati; Dina Fariza Tryani Syarif (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
All children can think. However, some of them have difficulties in optimizing their thinking functions on account of their level of intelligence is below of average. This study aims to describe the cognitive aspects possessed by children with intellectual barriers. It was a qualitative method, and the subjects were three people who belong to the second grade of elementary school. Results of this study show deficiencies in the ability to remember lessons at school. The level of below average intelligence is one of the causes the teachings given by the teacher is equivalent to lessons for first-grade students in elementary school. Even the equivalent of students in kindergarten. However, subjects can carry out other activities.